Sarocladium krotoszynense (Sarocladiaceae)—a new species associated with seeds of alien tree Acer negundo (Sapindaceae) in Poland - Patejuk, Katarzyna; Piątek, Marcin; Czachura, Paweł (Phytotaxa, 2026)
The genus Sarocladium (Hypocreales, Sarocladiaceae) includes acremonium-like hyphomycetes that produce elongated, phialidic conidiophores and aseptate, hyaline conidia. The genus contains species that inhabit soil and plants and cause animal and human infections. Some species produce bioactive metabolites with significant applications across pharmacy, medicine, and biotechnology. Recently, two strains of Sarocladium species were isolated from symptomatic seeds of alien Acer negundo trees growing in Krotoszyn town in western Poland and subjected to morphological and multi-gene (ITS, LSU, rpb2, tef1, act) phylogenetic analyses. The results showed that they represent species distinct from previously known Sarcocladium species, including the most closely related Sarocladium hyalosporum and S. mali. Therefore, a new species Sarocladium krotoszynense is described for the isolated fungus. Pathogenicity tests showed that S. krotoszynense has the ability to induce disease on leaves and seeds of Acer negundo.